INFLUENCE OF IRRIGATION METHODS AND REGIMES OF WINTER WHEAT VARIETIES ON THE AGROCHEMICAL PROPERTIES OF SOILS UNDER TYPICAL SIEROZEM CONDITIONS - Mamurova Nadira Ergashbayevna (Web of Journals Publishing, 2025)
In the conditions of typical sierozem soils of the Fergana region, subjected to irrigation erosion (slope level 1.50), data on the agrochemical properties of the soil, depending on the irrigation regime and methods of winter wheat varieties Davr and Vexa, are presented.
Keywords: Typical gray soils, irrigation erosion, winter wheat, Davr and Vexa varieties, irrigation regime, furrow irrigation, flexible pipe, soil horizons, humus, total nitrogen, total phosphorus, nitrate nitrogen, mobile phosphorus, exchangeable potassium.